All you want to know about the arrhythmia: A comprehensive, nationwide registry study of atrial fibrillation in Finland. (24th May 2021) - Lehto, M; Halminen, O; Haukka, J; Linna, M; Mustonen, P; Putaala, J; Itainen-Stromberg, S; Kinnunen, J; Kouki, E; Luojus, A; Niiranen, J; Penttila, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Helsinki and Uusimaa Hospital District Funding The Finnish Foundation for Cardiovascular Research OnBehalf: FinACAF Introduction: The number of atrial fibrillation (AF) patients is increasing, and thus, the socio-medico-economic impact of AF is exploding.  Up-to-date, multifaceted data about the characteristics of AF patients, their treatments, and outcomes are urgently needed. Purpose: The aim of the Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) study is to evaluate the incidence and prevalence of AF, risk of stroke, thromboembolic complications, myocardial infarction, major bleeding events, and mortality in AF patients using comprehensive nationwide registries regulated by law. Assessment of the socio-medico-economic aspects of AF and the effect of socio-economic factors on the AF treatment play a central role in this study. Methods: The FinACAF study collects data from 411 000 patients covering all Finnish AF patients from 1st January 2004 to 31st December 2018. Using national unique personal identification number, individual patient data from ten nationwide population registries and six regional laboratory databases (∼282000, 77 % of the patients) are linked together. All the register data were obtained during Q1-Q2/2020. The main results will be expected during Q1-2/2021. Results: Since the introduction of the national primary care register in 2012, 9% of all AF patients were identified outside hospital care registers. The total number of AF patients on 31st December 2018 was 227 114, which translates to an AF prevalence of 4.1% in Finland (population of 5 517 900). The Table represents the registries used in the FinACAF study. Conclusions: The FinACAF study records all patient contacts with the health care institutions and organizations, as well as incomes and places of domicile. Thus, the database allows a unique possibility to investigate the epidemiology and socio-medico-economic impact of AF as well as the cost effectiveness of different AF management strategies in a completely unselected, nationwide population. This data will markedly help "leading with data" when the increasing number of AF patients are treated.